C# programming : from problem analysis to program design - Doyle, Barbara (Australia Cengage Learning, 2014)
Only this book brilliantly balances today's most important programming principles and concepts with the latest insights into C#. This perfect introductory book highlights the latest Visual Studio 2012 and C# 4.0 with a unique, principles-based approach to give readers a deep understanding of programming. You'll find just the right amount of detail to create an important foundation in programming. This edition's straightforward approach and understandable vocabulary make it easier for readers to grasp new programming concepts without distraction. The book introduces a variety of fundamental programming concepts, from data types and expressions to arrays and collections, all using the popular C# language. New programming exercises and new numbered examples throughout this edition reflect the latest updates in Visual Studio 2012, while learning objectives, case studies and Coding Standards summaries in each chapter ensure mastery. While the book assumes no prior programming knowledge, coverage extends beyond traditional books to cover new advanced topics, such as portable class libraries used to create applications for Windows Phone and other platforms.
'Microsoft Visual C# 2012'--Cover.
Keywords: Computer programming; C# (Computer program language).; Internet programming; Object-oriented programming (Computer science).